"Broken and Useless". Notes on Fashion and Textile Recycling and Repurposing in 18th Century Venice. Issue 2 (4th May 2019) - Campagnol, Isabella
Abstract: In 18 th century Venice, a city renowned for its unparalleled opulence, judicious recycling and repurposing of luxury textiles, was, ironically, the norm. Archival documents routinely list elegant, but "worn out" items, as in the 1773 inventory of Marina Eirardi, where a number of broken and "useless" clothing items are mentioned, and where is carefully described what remains of a precious gown made with a "brocade fabric with gold and silver flowers … disassembled into pieces and the gold and silver flowers had been removed … so that holes remain in their places". While we do not know what happened to the flowers, it is anyway clear that these valuable elements were saved and somehow recycled, if only to melt down the precious metals. Comparing this document with an almost contemporary garment, the paper proposes to explore examples of patrician thriftiness, opening interesting avenues of investigations about the reuse of luxury items.